Sequential effects in Olympic synchronized diving scores - Kramer, R. S. S. (Royal Society Open Science, 2017)
When judging performances in a sequence, the current score is often influenced by the preceding score. Where athletes are perceived to be similar, a judgement is assimilated towards the previous one. However, if judges focus on the differences between the two athletes, this will result in a contrasting influence on their scores. Here, I investigate sequential effects during synchronized diving events at the 2012 and 2016 Olympic Games. Although previous research found assimilation in scores of gymnasts, the current data showed contrast effects—current scores benefited from following a poor performance but were at a disadvantage if they followed a high-scoring performance. One explanation may be that the processes involved in judging synchronized pairs results in a focus on the differences between athletes, producing a contrast effect across dives. That the specific direction of this sequential bias may depend on the particular sport has implications for how judges might approach their roles in a context-dependent manner, as well as how such biases should be addressed.